2022
DOI: 10.2174/1389201023666220307110554
|View full text |Cite
|
Sign up to set email alerts
|

Wedelolactone, a Component from Eclipta prostrata (L.) L., Inhibits the Proliferation and Migration of Head and Neck Squamous Cancer Cells through the AhR Pathway

Abstract: Background: Ecliptae prostrata (L.) L. has been widely used in east Asia with reported biological activities including anti-cancer properties. Objective: We aimed to investigate the effect of ethyl acetate extract of Ecliptae prostrata (L.) L. (EAE) and its component wedelolactone on the proliferation and migration of head and neck squamous cancer cells. Methods: The proliferation of human SCC-4 and mouse CU110-1 tongue squamous carcinoma cells was assessed using the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Research demonstrated that OB significantly mitigated lung histopathological injury, reduced the release of inflammatory cytokines, and decreased levels of Fe 2+ and 4-HNE, by inhibiting Nrf2 ubiquitination and upregulating the Nrf2/SLC7A11/GPX4 signaling pathway, ↑: up-regulation, increase or activation; ↓: down-regulation, decrease or inhibition ultimately inhibiting iron-dependent ferroptosis and alleviating LPS-induced ALI [131]. Wedelolactone (Wed) is the principal active component of Eclipta prostrata and is categorized as a lactone [132]. Research findings indicate that Wed mitigates pancreatitis and associated lung damage in mouse models induced by taurine cholate or small proteins.…”
Section: Acute Lung Injurymentioning
confidence: 99%
“…Research demonstrated that OB significantly mitigated lung histopathological injury, reduced the release of inflammatory cytokines, and decreased levels of Fe 2+ and 4-HNE, by inhibiting Nrf2 ubiquitination and upregulating the Nrf2/SLC7A11/GPX4 signaling pathway, ↑: up-regulation, increase or activation; ↓: down-regulation, decrease or inhibition ultimately inhibiting iron-dependent ferroptosis and alleviating LPS-induced ALI [131]. Wedelolactone (Wed) is the principal active component of Eclipta prostrata and is categorized as a lactone [132]. Research findings indicate that Wed mitigates pancreatitis and associated lung damage in mouse models induced by taurine cholate or small proteins.…”
Section: Acute Lung Injurymentioning
confidence: 99%
“…Studies have shown that multiple components of Ecliptae Herba have anti-tumor activities. [10][11][12][13] Yadav explored the inhibitory effects of Ecliptae Herba ethanol extract on 7 different cancer cell lines and found that the proliferation and migration of breast cancer cells were the most inhibited. [14] However, the mechanism of action of Ecliptae Herba in breast cancer treatment remains unknown.…”
Section: Introductionmentioning
confidence: 99%